THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEMS, PROCESS INNOVATION AND OPERATIONAL EFFICIENCY IN HOSPITALS - Anggilia Yuliani Susanti; Vip Paramarta; Farida Yuliaty; Kosasih; Fitriana; Sri Rochani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Hospital administration is facing increasing challenges in ensuring operational efficiency while maintaining the quality of healthcare services. The digital transformation in hospital administration, particularly through the implementation of Hospital Management Information Systems (SIMRS) and process innovations, has become a crucial strategy in improving service efficiency. SIMRS facilitates data integration, automates administrative tasks, and enhances coordination among hospital units, leading to faster and more accurate service delivery. However, its implementation faces obstacles such as limited technological infrastructure, staff readiness, and high implementation costs. Meanwhile, process innovation such as digital queue systems and automated administrative procedures, optimizes resource utilization and reduces patient waiting times. Despite these advantages, challenges like resistance to change and limited funding remain significant barriers. This study, conducted through a literature review, analyzes the relationship between SIMRS, process innovation, and hospital efficiency. The findings highlight the importance of comprehensive strategies, including policy support, staff training, and infrastructure development, to ensure effective digital transformation in hospital administration.